Mali : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2004)
This paper focuses on Mali's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. Mali's economic situation improved in 2003, in spite of a difficult regional environment. The IMF staff considers that the government's medium-term program, which is aligned to the Poverty Reduction Strategy Paper (PRSP) policy agenda, offers a strong framework for Mali to implement its poverty reduction strategy, pursue fiscal consolidation, and continue the reform process. The IMF staff also notes the progress made in implementing the PRSP, as indicated in the first annual progress report.